2012
DOI: 10.2478/v10240-012-0010-5
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of professional identity of university teachers: reflecting on the ideal university teacher

Abstract: The dynamics of professional identity of university teachers: reflecting on the ideal university teacher Current paper investigates development of professional identity of university teachers, observed through reflective exercises which enabled participants' to focus on their perception of the ideal university teacher. Images of the ideal university teacher were studied from two aspects: first - before the participants started teaching, and second - after they had been teaching for some time. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
0
13
0
2
Order By: Relevance
“…Professional identity is an individual's cultural and social self-formation process in the context of work [43]. The academic professional identity is multiple and often also fragmented because of the various local and international, research and teaching communities to which the teachers are connected [44].…”
Section: It Feels Empowering (Personal Notes)mentioning
confidence: 99%
“…Professional identity is an individual's cultural and social self-formation process in the context of work [43]. The academic professional identity is multiple and often also fragmented because of the various local and international, research and teaching communities to which the teachers are connected [44].…”
Section: It Feels Empowering (Personal Notes)mentioning
confidence: 99%
“…The problem of personality value qualities of an ideal higher education teacher has been studied by foreign scholars: A. Haamer, L. Lepp, E. Reva (2012); O. Dautova, O. Krylova (2016); M. Skrynnik (2014), S. Azer (2005) et al…”
Section: Students' Views On the Personality Value Qualities Of An Idementioning
confidence: 99%
“…Germany (Skrynnik, 2014) Estonia (Haamer, Lepp and Reva, 2012) Russia (Skrynnik, 2014) the USA (Azer, 2005) The overall results of the survey among the students of foreign higher education institutions are summarized in Table 1. It has been found that the respondents' answers specify most often such personality value qualities of an ideal higher education teacher as expertise in the relevant field, communication skills; the second position is taken by teaching tact, intelligence, empathy, emotional stability, openness; the third position is occupied by self-awareness, tolerance, knowledge of behavioural strategies, creativity, ability to build relationships with students; the fourth position is taken by mastery of teaching methodology, adherence of principles, organizational skills and readiness for leadership, responsibility and sense of humour.…”
Section: Country / Personality Value Qualities Of Academic Staffmentioning
confidence: 99%
“…Європейські дослідники [14] розглядають пра-гнення до професійного ідеалу як джерело і ресурс професійному розвитку. Згадані дослідження пока-зують: ідеальний викладач -це педагог, особистість, експерт предметних знань.…”
Section: виклад основного матеріалу щодо змісту сутності та структурunclassified
“…Естонські вчені дослідили трансформацію уявлень викладачів університету про ідеал впродовж 5 років від початку діяльності. За їх результатами, викладання вимагає не тільки книж-них, технічних знань, а мудрості, життєвого досвіду, світогляду [14]. Можна зробити висновок, що україн-ський ідеал викладача в цілому відповідає загально-європейському.…”
Section: виклад основного матеріалу щодо змісту сутності та структурunclassified